Initial TCV operation with a baffled divertor. (11th January 2021) - Reimerdes, H.; Duval, B.P.; Elaian, H.; Fasoli, A.; Février, O.; Theiler, C.; Bagnato, F.; Baquero-Ruiz, M.; Blanchard, P.; Brida, D.; Colandrea, C.; De Oliveira, H.; et al.
Abstract: The Tokamak à Configuration Variable (TCV) tokamak is in the midst of an upgrade to further its capability to investigate conventional and alternative divertor configurations. To that end, modular and removable gas baffles have been installed to decrease the coupling between the divertor and the plasma core. The baffles primarily seek to suppress the transit of recycling neutrals to closed flux surfaces. A first experimental campaign with the gas baffles has shown that the baffled divertor remains compatible with a wide range of configurations including snowflake and super- X divertors. Plasma density ramp experiments reveal an increase of the neutral pressure in the divertor by up to a factor ×5 compared to the unbaffled divertor and thereby qualitatively confirm simulations with the SOLPS-ITER code that were used to guide the baffle design. Together with a range of new and upgraded divertor diagnostics, the baffled TCV divertor is now used to validate divertor models for ITER and next step devices with particular emphasis on geometric variations.